ZnO nanorod arrays grown on g-C3N4 micro-sheets for enhanced visible light photocatalytic H2 evolution. Issue 42 (7th August 2019) - Qin, Hengfei; Zuo, Yuanhui; Jin, Jutao; Wang, Wenlong; Xu, Youlong; Cui, Lifeng; Dang, Haifeng
Abstract : The designed synthesis of photocatalysts with hierarchical heteroassemblies in a facile, mild and eco-friendly way becomes more and more important, since we can explore the novel properties and applications of novel heterostructures via this method. Abstract : The designed synthesis of noble-metal-free photocatalysts with hierarchical heteroassemblies in a facile, mild and eco-friendly way becomes more and more important, because we can explore the novel properties and applications of novel heterostructures via this method. Herein we report a two-step aqueous strategy for novel hierarchical heterostructures of ZnO nanorod (NR) arrays grown on graphitic carbon nitride (g-C3 N4 ). The novel g-C3 N4 /ZnO NR heterostructures that integrate g-C3 N4 and ZnO NR via high-quality g-C3 N4 –ZnO heterojunctions have beneficial properties such as high specific surface area (SSA), open spatial architecture, good electronic conductivity, and effective charge transfer interfaces, and are promising in many related areas such as water splitting, solar cells, etc. As a noble-metal-free and visible-light-responsive photocatalytic material, a typical g-C3 N4 /ZnO NR photocatalytic system exhibits enhanced photocatalytic activity toward H2 evolution, almost 3.5 times higher than that of pure g-C3 N4 . The superior photocatalytic property can be ascribed to the synergistic effect of the unique g-C3 N4 /ZnO NR heterostructures.